FAKTOR PEMENGARUH DAN PEMECAHANNYA DALAM PEMBELAJARAN MEMBACA-MENULIS PERMULAAN - Edy Suryanto; Purwadi Purwadi; Budi Waluyo (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
This study aimed to describe: 1) the implementation of learning to read-write for the beginners 2) to identify the influences factors, and 3) how to solve those factors of influences. The populations were students and one classroom teacher of SDN Cinderejo Surakarta. Data was collected through observation, interviews, and document analysis. Sampling determined through purposive sampling technique. The results of the study concluded: 1) RWB learning component involves students, teachers, objectives, materials, methods, media, and evaluation. Various components are interrelated. 2) Barriers to learning RWB included the internal and external obstacles. (3) To overcome internal barriers were done through learning process, while external barriers pursued through the outside component of the learning process in the classroom RWB.